2019
DOI: 10.1039/c9cc04257a
|View full text |Cite
|
Sign up to set email alerts
|

Highly-selective recognition of latent fingermarks by La-sensitized Ce nanocomposites via electrostatic binding

Abstract: A series of binuclear (Ce,La) nanocomposite fluorescent powders was elaborately designed for highly-selective recognition of latent fingermarks, which were proved to combine with fingermark residues electrostatically without any damage to touch-DNA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Typically, fluorescent nanomaterials have been highly concerned in forensic science during the last two decades on account of their excellent luminescent property, smaller particle size, versatile surface modification, and low toxicity. Lately, rare earth nanocrystals, perovskite nanostructures, fluorescent polymer nanoparticles, Mn 4+ -doped red emissive phosphors, , and aggregation-induced emission luminogens were continually reported as effective fingerprint developers. Nonetheless, their practical use for forensic investigation is still limited because of the complicated syntheses, expensive raw materials, or poisonous regents.…”
Section: Introductionmentioning
confidence: 99%
“…Typically, fluorescent nanomaterials have been highly concerned in forensic science during the last two decades on account of their excellent luminescent property, smaller particle size, versatile surface modification, and low toxicity. Lately, rare earth nanocrystals, perovskite nanostructures, fluorescent polymer nanoparticles, Mn 4+ -doped red emissive phosphors, , and aggregation-induced emission luminogens were continually reported as effective fingerprint developers. Nonetheless, their practical use for forensic investigation is still limited because of the complicated syntheses, expensive raw materials, or poisonous regents.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5] To this end, a mass of nanoparticles was reported as fingerprint developers, [6][7][8][9][10] such as iron, titanium, europium, cobalt and silicon oxides or their alloys. In addition, during the last decade, a variety of nanophosphors, including semiconducting metal/polymer dots, [11][12] organic aggregate luminogens, [13][14][15] rare earth-based powders, [16][17][18][19][20][21] metal-organic frameworks, [22][23][24] fluorescent carbon dots, [25][26][27][28][29][30][31][32][33] noble metal nanoclusters [34][35][36][37] and perovskite nanocrystals [38][39][40] have gradually become the mainstream for fingerprint development applications. In theory, the high or color-tunable fluorescence of nanophosphors can enhance the contrast of developed fingerprints on various backgrounds.…”
Section: Introductionmentioning
confidence: 99%
“…Since 19th century, fingerprints have been used as one of the most important means for criminal investigations and many studies have focused on the development of fingerprint detection techniques. [1] Among the emerging strategies, the use of luminescent nanoparticles, especially rare earth fluorescent nanomaterials, [2][3][4] gold nanoparticles [5,6] and quantum dots, [7,8] was regarded as the most notable one in the field. [9] It was found that small powder particles adhere better on fingermark residue and then the detected residue are easily observed in virtue of the fluorescent properties of nanomaterials.…”
Section: Introductionmentioning
confidence: 99%